A crop wild relative inventory for Southern Africa: A first step in linking conservation and use of valuable wild populations for enhancing food security - Allen, E.; Gaisberger, H.; Magos Brehm, Joana; Maxted, N.; Thormann, I.; Lupupa, T.; Dulloo, Mohammad Ehsan; Kell, S. (Cambridge University Press, 2019)
Successful conservation strategies require that taxa are prioritized because resources for planning and implementation are always limited. In this study, we created a partial checklist of crop wild relatives (CWR) that occur in the Southern African Development Community (SADC) region and identified the taxa of highest priority for regional conservation planning based on their importance for food and economic security. We found that the region contains over 1900 wild relatives of species cultivated for food, beverages, ornamental, forage/fodder, forestry, medicinal, environmental and other uses. Prioritization of these species was based on two criteria: (i) the value of the related crop for human food and economic security in the region and/or globally, and (ii) the potential or known value of the wild relatives of those crops for crop improvement. The region contains 745 CWR species related to 64 human food and beverage crops that are of high socioeconomic importance and 100 of these are of immediate priority for conservation action. The results of this study show that the SADC region contains a wealth of CWR diversity that is not only of value for food and economic security within the region but also globally. Furthermore, this study represents the first step in developing a CWR conservation and sustainable use strategy for the region, where its implementation would contribute to food security and well-being.